The Space Confinement Approach Using Hollow Graphitic Spheres to Unveil Activity and Stability of Pt‐Co Nanocatalysts for PEMFC. Issue 20 (14th July 2017) - Pizzutilo, Enrico; Knossalla, Johannes; Geiger, Simon; Grote, Jan‐Philipp; Polymeros, George; Baldizzone, Claudio; Mezzavilla, Stefano; Ledendecker, Marc; Mingers, Andrea; Cherevko, Serhiy; Schüth, Ferdi; Mayrhofer, Karl J. J.
Abstract: The performance of polymer electrolyte fuel cells is strongly correlated to the electrocatalytic activity and stability. In particular, the latter is the result of an interplay between different degradation mechanisms. The essential high stability, demanded for real applications, requires the synthesis of advanced electrocatalysts that withstand the harsh operation conditions. In the first part of this study, the synthesis of oxygen reduction electrocatalysts consisting of Pt‐Co (i.e., Pt5 Co, Pt3 Co, and PtCo) alloyed nanoparticles encapsulated in the mesoporous shell of hollow graphitic spheres (HGS) is reported. The mass activities of the activated catalysts depend on the initial alloy composition and an activity increase on the order of two to threefold, compared to pure Pt@HGS, is achieved. The key point of the second part is the investigation of the degradation of PtCo@HGS (showing the highest activity). Thanks to pore confinement, the impact of dissolution/dealloying and carbon corrosion can be studied without the interplay of other degradation mechanisms that would induce a substantial change in the particle size distribution. Therefore, impact of the upper potential limit and the scan rates on the dealloying and electrochemical surface area evolution can be examined in detail. Abstract : Hollow graphitic spheres are employed for confined space alloying of Pt‐Co nanocatalysts (i.e., Pt5 Co, Pt3 Co, and PtCo), whereas a two to threefold improvement in intrinsic activity and enhanced stability is achieved. Furthermore, dissolution/dealloying and carbon corrosion are investigated, while major degradation mechanisms are suppressed thanks to the mesoporous graphitic support material.